THE ROLE OF CONSIDERATION OF THE VALUE OF RISKS, SHAME AND GUILT IN UTILITARIAN MORAL JUDGMENT ON ACADEMIC DISHONESTY BEHAVIOR - Imaduddin Hamzah; Iman Santoso; Nazhifah Imaduddin (Jurnal Cakrawala Pendidikan, 2020)
Students generally know that cheating and plagiarism are violations of academic ethics, but some still do it. The study of academic dishonesty has been more into quantitative approaches, thus it cannot explain the dynamics of moral psychology about the decision making of cheating and plagiarism. This study explores the role of the consideration of the value of risk, shame, and guilt in utilitarian moral judgment in academic dishonesty behavior, as a solution to the views of theoretical debates about the role of emotions and cognitive morals in explaining good and bad behavior. This research used an interpretative phenomenological analysis approach to explore the meaning of the experience of conducting academic dishonesty by interviewing 66 college students. The results showed that ignorance of shame and the absence of guilt played a role in weakening the utilitarian moral judgment of students to act honestly in the face of examinations and assignments. These findings contributed to the importance of strengthening moral and ethical education for students in academic programs.